Treatment of Pimpinella Alpina Molk Improve Oxidative stress and Inhibit Liver Cellular Apoptosis in Rats Following UVB Irradiation: Is there Any Correlation? (Bangladesh Journal of Medical Science, 2018)
Objective: The effect of Pimpinella alpina Molk (PaM) in improvement of oxidative stress has been established, but did not for cellular apoptosis. This investigation was conducted to evaluate the effect of PaM on GPx and XO activities, hepatocytes apoptosis and their correlation following UVB radiation.Methods: Forty male rats were assigned into 8 groups: Nor-G, Neg- 7, Neg-15, PaM50-7, PaM100-7, PaM150-7, PaM100-15, and PaM150-15. UVB irradiation was given 10 minutes to each rat daily, blood and liver organ samples were taken in day 8 and day 16 to evaluate all variables.Results: Post Hoc statistical analysis showed that GPx activity in PaM150-15 was not significant lower compared to that of Nor-G, p > 0.05. Conversely, the activity of XO in PaM150-7 was not significant higher compared to that of Nor-G, p > 0.05. Expression of Bax and Caspase3 mRNA in PaM100-15 and PaM150 were comparable to that of Nor-G, p > 0.05. The strong negative correlation (-795, p < 0.01) was occur between GPx and XO. Similarly, there were strong negative correlations (-697 and -715, p < 0.001) between GPx and the expression of Bax and Caspase3 mRNA.Conclusion: PaM treatment with 100 - 150 mg daily dose for 15 days capable of improving oxidative stress marked by increase in GPx activity and decrease in XO activity and inhibit apoptosis characterized by decrease in the expression of Bax and caspase3 mRNA. There were strong negative correlations between antioxidant activity and apoptosis on Sprague male rats after UVB irradiation.Bangladesh Journal of Medical Science Vol.17(1) 2018 p.118-128